Beyond plasmid addiction: the role of toxin–antitoxin systems in the selfish behavior of mobile genetic elements - Mendoza Guido, Bradd (2025)
Toxin-antitoxin (TA) systems were initially described as “addiction” modules that promote plasmid maintenance through a post-segregational killing (PSK) mechanism. In this process, the cells are forced to retain plasmids to avoid death caused by the longer half-life of the toxin compared to the antitoxin. However, TA systems have since been widely identified across a broad range of mobile genetic elements (MGEs), suggesting that TA systems support the maintenance of these MGEs within bacterial hosts and contribute to the exclusion of competing MGEs such as plasmids and phages. This perspective highlights their broader role beyond plasmid addiction, functioning as key components in safeguarding MGE persistence and enhancing MGE fitness. Therefore, the concept of “plasmid addiction” should be reconsidered as a subset of a more comprehensive phenomenon referred to as “MGE selfishness,” which more accurately captures the widespread distribution and conserved, self-serving functions of TA systems across diverse MGEs. Additionally, TA systems facilitate the establishment of MGEs as “molecular symbionts” within bacterial cells. While initially considered parasitic, the relationships can evolve to provide mutual benefits for both the MGE and the host. From a gene-centered evolutionary perspective, the proposed molecular symbiosis may progress to a point where most of the MGE’s original content is lost, leaving only essential genes that are retained and functionally co-opted by the host. Further studies should investigate the role of TA systems in MGEs beyond plasmids, as well as their evolutionary trajectories toward specialized functions that may influence the adaptation and evolution of key bacterial groups, including pathogens.